New energy vehicle radiation shielding film and preparation process thereof

By using new two-dimensional materials such as polyester fiber, MXene and transition metal sulfides, a shielding film with multi-layer composite structure is designed, which solves the problems of large weight and poor flexibility of traditional electromagnetic shielding materials, and achieves efficient and lightweight electromagnetic shielding Effect, suitable for improving electromagnetic compatibility of new energy vehicles.

CN119431861APending Publication Date: 2025-02-14CHENGDU CHUANGXING SPACE ENTERPRISE MANAGEMENT CONSULTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506625.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional electromagnetic shielding materials have large weight and poor flexibility, which makes them difficult to adapt to complex vehicle body structures and have high production costs.

Method used

New two-dimensional materials such as polyester fiber, MXene and transition metal sulfide are used to form a multi-scale structure shielding film through multi-layer composite structure design, and the interface reinforcement layer is used to improve interlayer bonding force.

Benefits of technology

It realizes lightweight materials with excellent shielding performance in a wide electromagnetic spectrum range, significantly improves the electromagnetic compatibility of new energy vehicles, reduces the impact of electromagnetic interference on electronic systems, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431861A_ABST
    Figure CN119431861A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, and discloses a new energy vehicle radiation shielding film which comprises a two-dimensional material composite structure, the shielding film comprises a two-dimensional material composite structure, and the two-dimensional material composite structure comprises a polyester fiber layer, an MXene layer and a transition metal sulfide layer. All the layers of materials are mutually combined through the interface enhancement layer to form a multi-layer composite film structure, the interface enhancement layer is a self-assembled monomolecular layer SAM, all the two-dimensional material layers are connected through hydrogen bonds, electrostatic interaction or covalent bonds, and the interlayer binding force and the overall stability are enhanced. The novel two-dimensional materials such as polyester fibers, MXene and transition metal sulfide are adopted, and the multi-layer composite structure design is adopted, so that the shielding film has excellent shielding effectiveness in a wide electromagnetic spectrum range. By accurately controlling the layer number, the thickness and the interface bonding mode of the material, high-efficiency absorption and reflection of low-frequency to high-frequency electromagnetic waves are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new material technology, and specifically to a radiation shielding film for new energy vehicles and a preparation process thereof. Background Art

[0002] With the transformation of the global energy structure and the improvement of environmental awareness, new energy vehicles have become an important development direction of the future automotive industry. However, with the extensive application of high-power electronic devices such as motors, inverters, and large-capacity batteries, the electromagnetic environment inside new energy vehicles is becoming increasingly complex. Electromagnetic interference (EMI) has become an important factor restricting the safety and reliability of new energy vehicles. In severe cases, it may even affect the normal operation of on-board electronic equipment, resulting in reduced vehicle performance or potential safety hazards. Therefore, the development of efficient and lightweight electromagnetic shielding materials to reduce the impact of electromagnetic interference on new energy vehicles has become a technical problem that needs to be solved urgently in the industry.

[0003] Traditional electromagnetic shielding materials are mainly based on metals, including copper, aluminum, etc. Although these materials have good electromagnetic shielding performance, they have obvious disadvantages. First, the high density of metal materials leads to a heavy shielding structure, which is contrary to the development trend of lightweight new energy vehicles; secondly, metal materials have poor flexibility and are difficult to adapt to complex curved body designs, which limits their application in new energy vehicles; in addition, metal shielding materials usually require multiple complex processes during the manufacturing process, which increases production costs and time.

[0004] In view of the shortcomings of the existing technology, a radiation shielding film for new energy vehicles based on a new two-dimensional material and its preparation process are proposed. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a radiation shielding film for new energy vehicles and a preparation process thereof, which solves the problems of traditional electromagnetic shielding materials being heavy, poor in flexibility and difficult to adapt to complex vehicle body structures.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a radiation shielding film for new energy vehicles, the shielding film includes a layer of two-dimensional material composite structure, the two-dimensional material composite structure includes a layer of polyester fiber layer, a layer of MXene layer and a layer of transition metal sulfide layer, the layers of materials are combined with each other through an interface reinforcement layer to form a multi-layer composite membrane structure.

[0007] Specifically, the polyester fiber layer is prepared by a chemical vapor deposition (CVD) process, and a polyester fiber layer with high conductivity and excellent electromagnetic shielding performance is obtained by controlling the deposition time and reaction conditions. The MXene layer is peeled off from the MAX phase material by a wet etching process, and a uniform nanosheet layer is obtained by ultrasonic dispersion technology. The transition metal sulfide layer includes MoS2, which is formed by mechanical stripping or CVD, and has good electron mobility and an adjustable band structure.

[0008] Preferably, the interface enhancement layer is a self-assembled monolayer SAM, which connects the two-dimensional material layers through hydrogen bonds, electrostatic effects or covalent bonds to enhance interlayer bonding and overall stability.

[0009] Specifically, the self-assembled monolayer can be an organic molecule with specific functional groups, including thiol or phosphate compounds, which can form a tight molecular layer on the surface of the two-dimensional material, thereby improving the interfacial compatibility between layers, reducing interlayer debonding and slippage, and enhancing the mechanical stability of the overall structure.

[0010] Preferably, the shielding film has a multi-scale structural design, including nanoscale pores, wrinkles and surface roughness, to enhance the absorption and scattering of electromagnetic waves.

[0011] Specifically, nanoscale pores are achieved by controlling deposition conditions and material processing, and the wrinkled structure is formed by introducing stress during the deposition process or post-processing processes including stretching. These designs help absorb multi-band electromagnetic waves and improve the overall shielding effectiveness of the shielding film. In addition, the increase in surface roughness can effectively reduce the reflection of electromagnetic waves and further increase the absorption rate.

[0012] Preferably, the thickness of the shielding film is between 1 micron and 100 microns, the thickness of the polyester fiber layer is between 0.5 microns and 10 microns, the thickness of the MXene layer is between 1 micron and 20 microns, and the thickness of the transition metal sulfide layer is between 1 micron and 50 microns.

[0013] Specifically, the thickness of each layer is selected based on the test results of the electromagnetic shielding effectiveness of the material. The polyester fiber layer mainly provides high-frequency electromagnetic wave shielding, the MXene layer balances mechanical strength and electromagnetic shielding effectiveness, and the transition metal sulfide layer ensures the shielding effect of the material over the entire spectrum by adjusting the layer spacing and stacking method.

[0014] A preparation process of a radiation shielding film for a new energy vehicle comprises the following steps:

[0015] a) preparing a polyester fiber layer on a substrate by a roll-to-roll chemical vapor deposition (CVD) process;

[0016] b) preparing MXene by wet etching process and forming MXene layer by ultrasonic exfoliation, which was then coated on the polyester fiber layer;

[0017] c) preparing a transition metal sulfide layer by mechanical exfoliation or CVD and coating it on the MXene layer;

[0018] d) introducing a self-assembled monolayer SAM between the layers as an interface enhancement layer to ensure the interlayer bonding strength;

[0019] e) curing the multi-layer composite film by ultraviolet curing and heat treatment process to form a radiation shielding film with high electromagnetic shielding effectiveness;

[0020] f) Adding conductive particles, mainly Cu and Ni, to the composite film through an electroplating process to further improve the shielding effectiveness.

[0021] Specifically, during the preparation process, the CVD deposition conditions of the polyester fiber layer precisely control the gas flow, temperature and pressure to ensure the high crystallinity and conductivity of the polyester fiber layer. During the coating process of the MXene layer, a solution method combined with spin coating technology is used to ensure its uniform distribution and close integration with the underlying polyester fiber. The growth of the transition metal sulfide layer adopts a layer-by-layer stacking strategy, and by adjusting the deposition rate and atmosphere, a functional layer with uniform thickness and stable performance is formed.

[0022] Preferably, the polyester fiber layer is prepared by a roll-to-roll chemical vapor deposition (CVD) process, using copper foil or nickel foil as a substrate, and the deposition is performed within a temperature range of 1000° C. to 1100° C.

[0023] Specifically, the roll-to-roll process ensures the preparation of large-area, highly consistent polyester fiber films, and the substrates used include copper foil or nickel foil that has been cleaned and flattened to avoid defects during the deposition process. After deposition, the polyester fiber is transferred from the substrate to the target polymer substrate through electrochemical stripping technology to form a conductive layer with excellent electromagnetic shielding performance.

[0024] Preferably, the MXene layer is obtained by etching Ti3AlC2MAX phase material with LiF / HCl solution, the etching time is 12 hours to 48 hours, and the etching temperature is 25°C to 60°C.

[0025] Specifically, the preparation of MXene ensures the uniformity of the etching process by strictly controlling the concentration and temperature conditions of the etching solution, and uses ultrasonic stripping technology to ensure the uniform dispersion and high quality of the MXene flakes. Subsequently, the MXene dispersion is evenly coated on the polyester fiber layer by spraying or spin coating technology to enhance the electromagnetic shielding performance and mechanical strength of the composite film.

[0026] Preferably, the transition metal sulfide layer is prepared by mechanical stripping and chemical vapor deposition, the transition metal sulfide includes MoS2, and the thickness of the MoS2 layer is 1 micron to 50 microns.

[0027] Specifically, mechanical exfoliation is used to prepare high-quality MoS2 monolayer or multilayer sheets to ensure excellent electron mobility and interlayer stacking order. The MoS2 layers prepared by CVD can further adjust the interlayer spacing and thickness to meet specific electromagnetic shielding requirements, ultimately forming a multifunctional film that is both flexible and highly efficient.

[0028] Preferably, the curing time of the ultraviolet curing process is 10 seconds to 60 seconds, the curing temperature is 20°C to 60°C, the final heat treatment temperature of the multilayer composite film is between 200°C and 400°C, and the heat treatment time is 30 minutes to 3 hours.

[0029] Specifically, the UV curing process ensures that the coating layer cures quickly and has a smooth surface by adjusting the light source intensity and irradiation time. The curing process is carried out under low temperature conditions to avoid high temperature damage to the structure of the two-dimensional material and maintain the integrity and functionality of the film layer. The heat treatment process is carried out through gradual heating and temperature control and cooling steps to ensure the stress release between the layers of materials and the stability of the interface bonding. The optimization of heat treatment time and temperature further improves the conductivity and shielding effectiveness of the material while maintaining the mechanical strength and environmental stability of the film layer. The shielding film is cut into a suitable size and laid under the foot pad, like a layer of cloth, laid under the foot pad through the reception and the surface of the battery, isolating the battery below, providing some protection for the human body during long-term use in the car, and isolating the body from radiation.

[0030] Preferably, in step f, conductive particles Cu and Ni are added to the surface of the polyester fiber layer and the MXene layer of the composite membrane structure by an electroplating process, wherein the electroplating process includes controlling the current density at 0.5 A / dm 2 ~5A / dm 2 The electroplating time is 10 minutes to 60 minutes to ensure that the Cu and Ni particles are evenly distributed in the composite film, further enhancing the conductivity and electromagnetic shielding effectiveness of the shielding film.

[0031] The present invention provides a radiation shielding film for new energy vehicles and a preparation process thereof. It has the following beneficial effects:

[0032] 1. The present invention adopts new two-dimensional materials such as polyester fiber, MXene and transition metal sulfide, and through a multi-layer composite structure design, the shielding film has excellent shielding effectiveness in a wide range of electromagnetic spectrum. By precisely controlling the number of layers, thickness and interface bonding method of the material, efficient absorption and reflection of low-frequency to high-frequency electromagnetic waves are achieved, which significantly improves the electromagnetic compatibility of new energy vehicles in complex electromagnetic environments, effectively reduces the impact of electromagnetic interference in the vehicle on the electronic system, and ensures the safety and stable operation of the vehicle.

[0033] 2. The shielding film material of the present invention utilizes the mechanical strength of polyester fiber and MXene, and achieves an excellent weight-performance ratio through nano-scale multi-scale structural design. Compared with traditional metal-based shielding materials, the composite film of the present invention not only significantly reduces the weight of the material, which is in line with the trend of lightweight new energy vehicles, but also enhances the flexibility and fatigue resistance of the film by introducing surface roughness and pleated structure, adapting to the complex deformation requirements of the vehicle body, and providing greater freedom for the design of new energy vehicles.

[0034] 3. The present invention successfully realizes the efficient and low-cost production of two-dimensional material composite films through innovative roll-to-roll chemical vapor deposition CVD, wet etching and multi-layer coating technology, and ensures the consistency and high quality of the products. Combined with UV curing and optimized heat treatment process, the prepared shielding film shows excellent stability in harsh environments such as high temperature, high humidity and ultraviolet radiation, prolonging the service life of the material, improving the reliability of the product, and meeting the application requirements of new energy vehicles in various harsh use environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Please refer to the attached Figure 1 :

[0038] Example 1: Structure and material selection of radiation shielding film for new energy vehicles

[0039] The present invention provides a radiation shielding film for new energy vehicles based on a novel two-dimensional material, which is composed of a multi-layer two-dimensional material composite structure, specifically including a polyester fiber layer, a MXene layer and a transition metal sulfide (TMDs) layer. These layers are tightly combined through an interface enhancement layer (including a self-assembled monolayer, SAM) to form a composite film with high efficiency electromagnetic shielding.

[0040] Material selection:

[0041] Polyester fiber layer: High-quality single-layer or multi-layer polyester fibers are selected. The conductively treated polyester fibers are used as the main conductive layer of the shielding film due to their excellent conductivity and extremely low thickness. The conductivity and high-frequency electromagnetic wave shielding effectiveness of polyester fibers make them an important part of the present invention.

[0042] MXene layer: MXene materials (including Ti3C2T_x) have extremely high conductivity and controllable surface chemical properties. The MXene flakes prepared by wet etching are combined with the polyester fiber layer to form a multifunctional composite layer with enhanced electromagnetic shielding effectiveness.

[0043] Transition metal sulfide layer: including MoS2, which has excellent layered structure and tunable electronic properties. The MoS2 layer prepared by mechanical exfoliation or CVD method can further improve the shielding performance of the composite film in different frequency bands.

[0044] Multi-layer structure design:

[0045] Multi-scale structure: In order to improve the shielding effectiveness of shielding films against electromagnetic waves of different frequencies, multi-scale structures with nanopores, wrinkles and surface roughness are designed. These structures not only increase the absorption and scattering of electromagnetic waves, but also improve the mechanical flexibility of the material.

[0046] Interface reinforcement layer: Self-assembled monolayer SAM is used as the interface reinforcement layer between the two-dimensional materials. The layers of materials are connected through hydrogen bonds, electrostatic effects or covalent bonds to ensure the stability of the interlayer bonding and improve the overall mechanical strength of the material.

[0047] Example 2: Preparation process of radiation shielding film for new energy vehicles

[0048] The present invention provides a process for preparing the above-mentioned radiation shielding film for new energy vehicles, and the specific steps include:

[0049] Step 1: Preparation of the polyester fiber layer

[0050] Substrate preparation: Copper foil or nickel foil is used as the substrate for the growth of polyester fibers. The substrate is first chemically cleaned to remove surface oxides and impurities to ensure high-quality growth of polyester fibers.

[0051] CVD growth: The polyester fiber layer is deposited on the copper foil or nickel foil using a roll-to-roll chemical vapor deposition (CVD) process. The growth temperature is controlled between 1000°C and 1100°C, with methane (CH4) as the carbon source and hydrogen (H2) as the reducing atmosphere. The deposition time is adjusted according to the desired thickness of the polyester fiber layer.

[0052] Stripping and transfer: The deposited polyester fiber is stripped from the substrate and transferred to the final substrate, including polymer film. The stripping process uses wet transfer technology to remove the metal substrate through hydrofluoric acid (HF) solution.

[0053] Step 2: Preparation of MXene layer

[0054] Preparation of MAX phase materials: Ti3AlC2MAX phase materials were synthesized by high-temperature solid-phase reaction, which served as precursors of MXene.

[0055] Wet etching: Ti3AlC2 is etched using HF or LiF / HCl solution. The etching process is carried out in the temperature range of 25°C to 60°C for 12 to 48 hours to remove the Al element and form a two-dimensional Ti3C2T_xMXene sheet.

[0056] Ultrasonic exfoliation and dispersion: The MXene flakes are dispersed in the solvent by ultrasonic-assisted exfoliation technology, and then the unreacted MAX phase is removed by centrifugal separation to prepare a uniform MXene dispersion.

[0057] Step 3: Preparation of transition metal sulfide layer

[0058] Mechanical exfoliation of MoS2: Single or multilayer MoS2 was prepared by mechanical exfoliation, where MoS2 flakes were peeled off from the bulk material and transferred to the substrate using an adhesive tape.

[0059] CVD method to grow MoS2: or use chemical vapor deposition method to deposit MoS2 layer on the substrate through the reaction of molybdenum sulfide (MoO3) and sulfur (S), and the growth temperature is controlled between 600℃ and 800℃.

[0060] Step 4: Coating and curing of multi-layer structures

[0061] Multilayer coating: Use roller coating, spray coating and screen printing technology to coat each layer of material (polyester fiber, MXene, MoS2) on the substrate in sequence, ensuring the uniform distribution and required thickness of each layer of material. Use a laser thickness gauge to monitor the coating thickness in real time, and control the thickness of each layer of material by adjusting the coating speed and solution concentration.

[0062] Introduction of interface enhancement layer: A self-assembled monolayer SAM is introduced between each layer of two-dimensional material to form a stable interface enhancement layer through a molecular self-assembly process to ensure close bonding between the layers.

[0063] UV curing and heat treatment: The coated multilayer structure film is quickly cured by UV curing technology, with the curing time controlled between 10 and 60 seconds and the curing temperature between 20°C and 60°C. The cured multilayer film is then heat treated at a temperature of 200°C to 400°C for 30 minutes to 3 hours to enhance the overall mechanical properties and electromagnetic shielding effectiveness of the film.

[0064] Step 5: Addition of Conductive Particles

[0065] Electroplating process: Conductive particles, mainly Cu and Ni, are added to the composite film through electroplating process, and the electroplating current density is controlled at 0.5-5A / dm 2 The electroplating time is 10 to 60 minutes. Through this process, Cu and Ni particles are evenly distributed in or on the polyester fiber layer and the MXene layer to further improve the conductivity and electromagnetic shielding effectiveness of the shielding film.

[0066] Example 3: Performance testing and optimization of composite materials

[0067] Electromagnetic shielding effectiveness test:

[0068] Test method: Electromagnetic compatibility (EMC) test equipment is used to test the shielding effectiveness of composite materials in multiple frequency bands within the frequency range of 1MHz to 100GHz. The shielding effectiveness of materials is measured using a GTEM cell, and the reflection, transmission and absorption coefficients of materials for electromagnetic waves of different frequencies are measured using a network analyzer, and the shielding effectiveness (SE) value is calculated.

[0069] Result analysis and optimization: According to the shielding effectiveness test results, the number of layers, thickness and structure (including nanopores, wrinkles, etc.) of the composite material are adjusted to optimize the shielding performance of the material in different frequency bands, especially for radio waves in the 2.4GHz and 5GHz frequency bands, to improve the shielding effectiveness.

[0070] Mechanical properties test:

[0071] Test items: including tensile strength test, bending test and fatigue life test. The tensile strength and elongation of the composite material are measured by a tensile tester, and the flexibility of the material and its ability to maintain performance after multiple bending are evaluated by a bending tester.

[0072] Performance improvement: Based on the test results, optimize the material formulation and interface bonding strategy to ensure the mechanical strength and long-term durability of the composite materials in practical applications.

[0073] Environmental adaptability test:

[0074] High temperature and high humidity test: The composite material is placed in a constant temperature and humidity chamber at 85°C and 85% RH for long-term aging testing. The electromagnetic shielding effectiveness and mechanical properties of the material are measured regularly to evaluate the environmental adaptability of the material.

[0075] UV aging test: Use a UV aging test chamber to simulate long-term UV exposure conditions to test the performance changes of composite materials before and after aging, determine the material degradation mechanism through surface chemical analysis, and perform antioxidant treatment to extend the environmental tolerance of the material.

[0076] Thermal conductivity test:

[0077] Thermal conductivity measurement: Laser flash analysis is used to measure the thermal conductivity of composite materials, and infrared thermal imaging technology is used to evaluate the heat dissipation effect of the material under high power conditions.

[0078] Heat dissipation management optimization: Introduce high thermal conductivity materials (including boron nitride nanosheets) into composite materials, optimize the heat conduction path, and design the heat dissipation structure through thermodynamic simulation to ensure the thermal stability of the material during operation.

[0079] Example 4: Practical application and industrial production

[0080] New energy vehicle applications:

[0081] Full vehicle electromagnetic compatibility test: The developed shielding film is applied to key parts of new energy vehicles such as battery packs, control modules and motors to conduct full vehicle electromagnetic compatibility tests. Standard electromagnetic compatibility test equipment is used to evaluate the electromagnetic shielding effect of the whole vehicle under different working conditions to ensure the actual application performance of the shielding film.

[0082] Application feedback and optimization: Based on the feedback information from actual use, the material thickness, number of layers and installation method are adjusted in a targeted manner to further optimize the performance of the shielding film to meet actual needs.

[0083] Industrialized production and cost control:

[0084] Production line design: Based on the above laboratory process, a roll-to-roll production line suitable for industrial production is designed, including multi-layer coating, UV curing, heat treatment and cutting. The production line adopts automated control to ensure efficient large-scale production while maintaining consistent product quality.

[0085] Cost optimization strategy: Reduce production costs and ensure the market competitiveness of shielding films by purchasing raw materials on a large scale, optimizing process parameters and improving production efficiency.

[0086] Technology transformation and market promotion:

[0087] Technical cooperation: Cooperate with new energy vehicle manufacturers to apply shielding films to actual production models, and promote the widespread application of shielding films through technical support and application optimization.

[0088] Market promotion and standard setting: Actively participate in the formulation of industry standards for electromagnetic shielding materials, and promote products through exhibitions, academic conferences and online media to increase market influence and acceptance.

[0089] Summarize

[0090] The present invention provides a radiation shielding film for new energy vehicles based on a new two-dimensional material and a preparation process thereof. Through scientific material selection, structural design, process development and performance optimization, a lightweight composite material with high-efficiency electromagnetic shielding performance is successfully developed, and its industrial application in new energy vehicles is realized. The shielding film of the present invention has excellent electromagnetic shielding effectiveness, mechanical properties and environmental adaptability, can significantly improve the electromagnetic compatibility of new energy vehicles, and meet their lightweight and high-efficiency requirements.

[0091] Comparative Experimental Design

[0092] Experiment 1: Electromagnetic shielding effectiveness comparison experiment

[0093] Purpose:

[0094] By comparing the electromagnetic shielding effectiveness of the new energy vehicle radiation shielding film of the present invention with that of traditional metal-based shielding materials (including aluminum foil and copper foil) in different frequency bands, the superiority of the present invention in multi-band electromagnetic shielding performance is verified.

[0095] Existing technology (traditional metal-based shielding materials):

[0096] Traditional electromagnetic shielding materials, including aluminum foil and copper foil, have good electrical conductivity and are often used in electromagnetic shielding applications. However, due to their heavy weight and reduced performance at high-frequency electromagnetic waves (including GHz levels), their application in lightweight new energy vehicles is limited.

[0097] Technical solution of the present invention:

[0098] The present invention adopts a multilayer composite structure of polyester fiber, MXene and transition metal sulfide, and realizes high-efficiency, multi-band electromagnetic shielding through sophisticated interlayer design and interface reinforcement layer.

[0099] Comparison process design:

[0100] Sample preparation:

[0101] Traditional metal-based materials: Aluminum foil and copper foil samples with a thickness of 50 μm were prepared.

[0102] Shielding film of the present invention: According to the process in Example 1, a polyester fiber-MXene-MoS2 composite film with a thickness of 50 μm is prepared.

[0103] Test frequency band:

[0104] Six frequency bands, namely 1 MHz, 10 MHz, 100 MHz, 1 GHz, 10 GHz and 100 GHz, were selected and the shielding effectiveness (SE) of each sample was measured using a network analyzer and a GTEM cell.

[0105] Experimental parameters:

[0106] Sample size: 50mmx50mm

[0107] Incident electromagnetic wave angle: vertical incidence

[0108] Ambient temperature: 25℃

[0109] Humidity: 50%RH

[0110] Data Records:

[0111] Measure the shielding effectiveness in different frequency bands and record the SE value in each frequency band.

[0112] Data table:

[0113]

[0114]

[0115] Experimental conclusion:

[0116] The shielding effectiveness of the shielding film of the present invention in the low-frequency to high-frequency bands is significantly better than that of traditional aluminum foil and copper foil, and in particular, it shows more excellent performance in the high-frequency band (GHz level), indicating its application advantages in complex electromagnetic environments.

[0117] Experiment 2: Mechanical properties comparison experiment

[0118] Purpose:

[0119] By comparing the differences in mechanical properties (including tensile strength, flexibility, and fatigue resistance) between the shielding film of the present invention and existing metal mesh composite shielding materials, it is verified that the shielding film of the present invention has superior mechanical properties while maintaining high shielding effectiveness.

[0120] Existing technology (metal mesh composite material):

[0121] Metal mesh composite materials are usually composed of metal mesh and polymer matrix, which have certain flexibility and tensile strength. However, metal mesh materials are prone to breakage under multiple bending or stress, resulting in reduced shielding effectiveness.

[0122] Technical solution of the present invention:

[0123] The present invention utilizes the high conductivity and mechanical strength of polyester fibers and MXene, combined with a transition metal sulfide layer, to provide efficient electromagnetic shielding and excellent mechanical flexibility through multi-scale structural design and interface enhancement.

[0124] Comparison process design:

[0125] Sample preparation:

[0126] Metal mesh composite material: A composite material comprising copper mesh and polyester substrate was prepared with a thickness of 100 μm.

[0127] The shielding film of the present invention: a polyester fiber-MXene-MoS2 composite film with a thickness of 100 μm is prepared.

[0128] Test items:

[0129] Tensile Strength: Use a tensile testing machine to measure the maximum tensile strength and elongation at break of a material.

[0130] Bending flexibility: Multiple bending tests (180° repeated bending 500 times) were performed to evaluate the flexibility and fatigue resistance of the material.

[0131] Fatigue life: Fatigue testing is performed under cyclic stress to measure the fatigue life of the sample.

[0132] Experimental parameters:

[0133] Sample size: 10mmx100mm

[0134] Bending angle: 180°

[0135] Bending times: 500 times

[0136] Stretching speed: 5mm / min

[0137] Data Records:

[0138] The tensile strength, elongation at break, electromagnetic shielding effectiveness retention rate after bending and fatigue life of each sample were recorded.

[0139] Data table:

[0140] project Metal mesh composite materials Shielding film of the present invention Tensile strength(MPa) 100 150 Elongation at break (%) 10 15 SE retention rate after bending (%) 70 95 Fatigue life (times) 1000 5000

[0141] Experimental conclusion:

[0142] The shielding film of the present invention is superior to traditional metal mesh composite materials in terms of tensile strength, elongation at break and shielding effectiveness retention after bending, and the fatigue life is significantly extended, demonstrating its excellent performance and durability in complex mechanical stress environments.

[0143] Experiment 3: Environmental adaptability comparison experiment

[0144] Purpose:

[0145] By comparing the environmental stability of the shielding film of the present invention with that of existing coated shielding materials under high temperature, high humidity and ultraviolet irradiation, the stability and durability of the present invention in extreme environments are verified.

[0146] Existing technology (coated shielding material):

[0147] Coated shielding materials are usually prepared by coating conductive ink or metal coating on a substrate. Although the initial shielding effectiveness is good, they are easily degraded under high temperature, high humidity and ultraviolet radiation, resulting in a decrease in shielding performance.

[0148] Technical solution of the present invention:

[0149] The shielding film of the present invention is prepared by ultraviolet light curing and optimized heat treatment process, and has good interface bonding and chemical stability, so that it can still maintain excellent electromagnetic shielding effectiveness under extreme environments.

[0150] Comparison process design:

[0151] Sample preparation:

[0152] Coating material: A shielding film with conductive ink coated on a polyester substrate was prepared with a thickness of 50 μm.

[0153] The shielding film of the present invention: a polyester fiber-MXene-MoS2 composite film with a thickness of 50 μm is prepared.

[0154] Test environment:

[0155] High temperature test: Place the sample at 85℃ for 1000 hours and measure the shielding effectiveness regularly.

[0156] High humidity test: Place the sample in a humidity environment of 85% RH for 1000 hours and measure the shielding effectiveness regularly.

[0157] Ultraviolet radiation test: at UV intensity of 100W / m 2 The samples were exposed to UV light for 500 hours and the shielding effectiveness was measured regularly.

[0158] Experimental parameters:

[0159] Sample size: 50mmx50mm

[0160] Ambient temperature: 25℃ (except high temperature test)

[0161] UV irradiation wavelength: 280-400nm

[0162] Data Records:

[0163] Record the change of shielding effectiveness over time in different environments.

[0164] Data table:

[0165]

[0166] Experimental conclusion:

[0167] The shielding film of the present invention has a significantly better shielding effectiveness retention rate under high temperature, high humidity and ultraviolet irradiation conditions than traditional coated shielding materials, showing excellent environmental stability and durability, proving its strong adaptability in harsh use environments and suitability for use under various extreme conditions.

[0168] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Radiation shielding film for new energy vehicles, characterized in that: The shielding film includes a two-dimensional material composite structure, which includes a polyester fiber layer, a MXene layer and a transition metal sulfide layer. The layers of materials are combined with each other through an interface reinforcement layer to form a multi-layer composite membrane structure.

2. The radiation shielding film for new energy vehicles according to claim 1, characterized in that: The interface enhancement layer is a self-assembled monolayer SAM, which connects the two-dimensional material layers through hydrogen bonds, electrostatic effects or covalent bonds to enhance the interlayer bonding force and overall stability.

3. The radiation shielding film for new energy vehicles according to claim 1, characterized in that: The shielding film has a multi-scale structural design, including nanoscale pores, wrinkles and surface roughness, to enhance the absorption and scattering of electromagnetic waves.

4. The radiation shielding film for new energy vehicles according to claim 1, characterized in that: The thickness of the shielding film is between 1 micron and 100 microns, the thickness of the polyester fiber layer is between 0.5 microns and 10 microns, the thickness of the MXene layer is between 1 micron and 20 microns, and the thickness of the transition metal sulfide layer is between 1 micron and 50 microns.

5. A preparation process of a radiation shielding film for a new energy vehicle, according to the radiation shielding film for a new energy vehicle according to claims 1-4, characterized in that: The following steps are involved: a) preparing a polyester fiber layer on a substrate by a roll-to-roll process; b) preparing MXene by wet etching process and forming MXene layer by ultrasonic exfoliation, which was then coated on the polyester fiber layer; c) preparing a transition metal sulfide layer by mechanical exfoliation or CVD and coating it on the MXene layer; d) introducing a self-assembled monolayer SAM between the layers as an interface enhancement layer to ensure the interlayer bonding strength; e) curing the multi-layer composite film by ultraviolet curing and heat treatment process to form a radiation shielding film with high electromagnetic shielding effectiveness; f) Adding conductive particles, mainly Cu and Ni, to the composite film through an electroplating process to further improve the shielding effectiveness.

6. The preparation process of a radiation shielding film for new energy vehicles according to claim 5, characterized in that: The polyester fiber layer is prepared by a roll-to-roll process, using copper foil or nickel foil as a substrate, and is processed within an appropriate temperature range.

7. The preparation process of a radiation shielding film for new energy vehicles according to claim 5, characterized in that: The MXene layer is obtained by etching Ti3AlC2MAX phase material with LiF / HCl solution, the etching time is 12 to 48 hours, and the etching temperature is 25°C to 60°C.

8. The process for preparing a radiation shielding film for new energy vehicles according to claim 5, characterized in that: The transition metal sulfide layer is prepared by mechanical stripping and chemical vapor deposition, the transition metal sulfide includes MoS2, and the thickness of the MoS2 layer is 1 micron to 50 microns.

9. The process for preparing a radiation shielding film for new energy vehicles according to claim 5, characterized in that: The curing time of the ultraviolet curing process is 10 seconds to 60 seconds, the curing temperature is 20° C. to 60° C., the final heat treatment temperature of the multilayer composite film is between 200° C. and 400° C., and the heat treatment time is 30 minutes to 3 hours.

10. The preparation process of a radiation shielding film for new energy vehicles according to claim 5, characterized in that: In step f, conductive particles Cu and Ni are added to the surface of the polyester fiber layer and the MXene layer of the composite membrane structure by an electroplating process, wherein the electroplating process includes controlling the current density at 0.5 A / dm 2 ~5A / dm 2 The electroplating time is 10 minutes to 60 minutes to ensure that the Cu and Ni particles are evenly distributed in the composite film, further enhancing the conductivity and electromagnetic shielding effectiveness of the shielding film.